Héðinsdalsjökull, northern Iceland: geomorphology recording the recent complex evolution of a glacier - Rodríguez-Mena, Manuel (2021)
The objective of this work is to conduct a detailed mapping of the Héðinsdalsjökull foreland, northern Iceland (65°39′N, 18°55′W). This cirque currently shows a variety of glacial and periglacial landforms derived from a complex deglaciation. Mapping was performed combining traditional hand-drawn and digital mapping. A hand-drawn sketch was georeferenced in ArcMap 10.7.1, supported on an aerial photograph (year 2000). Its vectorization, symbolization and final design were done in the computer-aided design (CAD) software MicroStation Connect. Complementary high-resolution Digital Surface Models were obtained from historical aerial photographs and ground-view field photographs through the application of Structure from Motion (SfM) photogrammetry. To improve the topographic expression of the geomorphological map, a photorealistic 3D view has been generated. The final map highlights the complexity of the foreland and the coexistence existence of a range of different units and landforms. The map will ease future studies on the transformation of receding glaciers.